2005
DOI: 10.1093/annonc/mdi159
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant treatment for elderly patients with stage III colon cancer in the southern Netherlands is affected by socioeconomic status, gender, and comorbidity

Abstract: Although an increasing proportion of elderly patients with colon cancer are treated with adjuvant chemotherapy, many elderly patients still do not receive this treatment. As expected, receipt of adjuvant treatment decreased in the presence of comorbidity, but the clinical rationale for undertreatment of women and patients with low socioeconomic status is not clear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
70
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(81 citation statements)
references
References 25 publications
9
70
1
1
Order By: Relevance
“…15,18,26 -29 The proportion of untreated patients was particularly high among patients with metastatic solid tumors 26 and was most notable among patients older than age 70 years 15,27 and older than age 75 years. 18,28,29 Although guidelines suggest that chemotherapy should be reserved for patients with a good PS, 47 of 108 chemotherapy-treated patients in the current study had a PS Ն2. Therefore, we analyzed factors that were associated with receiving chemotherapy in the evaluated population.…”
Section: Discussionmentioning
confidence: 68%
“…15,18,26 -29 The proportion of untreated patients was particularly high among patients with metastatic solid tumors 26 and was most notable among patients older than age 70 years 15,27 and older than age 75 years. 18,28,29 Although guidelines suggest that chemotherapy should be reserved for patients with a good PS, 47 of 108 chemotherapy-treated patients in the current study had a PS Ն2. Therefore, we analyzed factors that were associated with receiving chemotherapy in the evaluated population.…”
Section: Discussionmentioning
confidence: 68%
“…3,14 Nevertheless, data from Europe suggest that in the year 2000, only 20% to 25% of elderly patients received adjuvant chemotherapy. 5,26,27 When studied, older patients have indicated that the primary determinant of their decision regarding chemotherapy was their physician's advice. 28 The physician's attitude may explain the low utilization of adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…[12] There are several explanations why elderly patients receive adjuvant chemotherapy less often than younger patients, such as the presence of comorbidities, unfavourable performance status or patient refusal. [38][39][40] Our study is hampered by the lack of information about comorbidities and performance status of the patient at time of diagnoses. Nevertheless marked differences in performance status of patients between hospitals in the Netherlands have not been reported.…”
Section: Accepted Manuscriptmentioning
confidence: 99%